SISTEM INFORMASI PENGGAJIAN KARYAWAN BERBASIS DESKTOP PADA DHEAMBUN PROJECT - Sari, Mayang; Ginting, Gerinata (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
This research aims to analyze, design, implement, and test a payroll information system for the Dheambun Project. The system is intended to simplify and automate the payroll process within the Dheambun Project company, ensuring accuracy and efficiency in managing employee salary data. The data sources used in this study include primary and secondary data. The research methodology employed is both quantitative and qualitative, utilizing research instruments such as interviews, observations, and literature studies. The data analysis technique used is the PIECES analysis method, while system development is carried out using the Waterfall model. The stages involved in system development include analyzing system weaknesses and needs; designing the Interface; and implementing it using Visual Studio 2015 as the programming language and MySQL as the database; testing is conducted using the Blackbox Testing method. The results of this research indicate that the implementation of the desktop-based payroll information system for the Dheambun Project operates effectively and meets its intended functions as per the proposed design.